Design factors contributing to active urban squares in Malaysia - Zakariya, Khalilah; Harun, Nor Zalina; Mansor, Mazlina (2016)
Urban squares are a type of public open space that cater for various activities for the public, such as for events and leisure. The activities in the square are not only contributed by annual events and celebrations, but also daily and weekly informal activities of visitors and tourists. Some squares even become landmarks and focal points of the city. While the design of urban squares has been studied in depth by researchers in other countries, however, local studies that interrogate how urban squares are occupied in Malaysia are still scarce. This research examines three prominent urban squares, which are Dataran Putra, Dataran Merdeka and Dataran Pahlawan, to explore and outline the key criteria that contribute to the activities of the squares. The research objectives are: 1) To identify the spaces, design elements, structures and surrounding area; 2) To map the activities and flow of users throughout the day; and 3) To synthesize the key findings to formulate design strategies for urban squares in Malaysia. The methods adopted for this research comprise of conducting site inventory and photographic documentation, observation and mapping, and semi-structured interviews with 150 visitors. The analysis reveals that there are five (5) key criteria that contribute to an active urban square. The findings from this research are useful for Landscape Architects and Urban Designers in planning and designing urban squares in Malaysia, or upgrading underutilized urban squares. This research concludes that an active and successful urban square can contribute to the city’s livability and quality of life for its people. In order to remain active and successful, urban square designs in Malaysia should meet the needs of the local climatic and socio-cultural factors.